Method for preparing microporous layer for fuel cell from nanocellulose modified carbon black

By using nanocellulose modified carbon black in the gas diffusion layer of the fuel cell, the modified microporous layer is formed, and the problems of insufficient porosity, pore size distribution and breathability of the microporous layer are solved, and the performance of the fuel cell is significantly improved.

CN119725571APending Publication Date: 2025-03-28ZHEJIANG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411923860.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the gas diffusion layer of the existing fuel cells, the porosity, pore size distribution and breathability of the microporous layer are insufficient, which affects the power performance and water management performance of the fuel cells.

Method used

Nanocellulose modified carbon black is used to configure nanocellulose solution and carbon black, spray it evenly on the surface of carbon paper, and sintered by heat treatment to form a modified microporous layer.

Benefits of technology

The porosity, pore size distribution and breathability of the microporous layer are improved, thereby improving the performance of the gas diffusion layer and improving the battery mass transfer capability of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725571A_ABST
    Figure CN119725571A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a microporous layer for a fuel cell from nano-cellulose modified carbon black, which comprises the following steps: 1, preparing 0.1-2.5 wt% of nano-cellulose solution, uniformly dispersing carbon black in the nano-cellulose solution with the concentration of 2-6 wt%, then adding polytetrafluoroethylene into the solution until the concentration is 20-40 wt%, and uniformly stirring to obtain a nano-cellulose solution; modified carbon black slurry is obtained; step 2, uniformly spraying the modified carbon black slurry onto the surface of carbon paper and ensuring that the carbon loading capacity of the surface of the carbon paper reaches 1mg / cm < 2 >-1.5 mg / cm < 2 >, and then drying at room temperature; and step 3, after drying, putting the carbon paper into a muffle furnace at 240-260 DEG C, keeping for 20-40 minutes to remove an active agent on the surface of polytetrafluoroethylene, then heating to 340-360 DEG C at a heating rate of 3-8 DEG C / min, and keeping the temperature for 20-40 minutes, so that the polytetrafluoroethylene is sintered and firmly bonded with carbon black particles in the carbon paper to obtain a microporous layer. The porosity, pore size distribution and air permeability of the microporous layer can be improved, and then the performance of the gas diffusion layer can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon paper, and in particular to a method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose. Background Art

[0002] The gas diffusion layer is one of the core components of the proton exchange membrane fuel cell. The gas diffusion layer includes a substrate layer and a microporous layer. The substrate layer is generally made of carbon paper, and the microporous layer is a material with a microporous structure. The microporous layer is generally arranged between the catalyst layer and the substrate layer. It is used to improve the interface between the catalyst layer and the substrate layer, provide gas transmission and discharge of water vapor generated by the reaction. Therefore, the microporous layer has an important influence on the power performance and water management performance of the fuel cell. Therefore, how to improve the porosity, pore size distribution and air permeability of the microporous layer is the key to preparing a high-performance gas diffusion layer. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose. The present invention can improve the porosity, pore size distribution and air permeability of the microporous layer, thereby improving the performance of the gas diffusion layer.

[0004] The technical solution of the present invention is a method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, comprising the following steps:

[0005] Step 1, preparing a 0.1-2.5wt% nanocellulose solution, uniformly dispersing carbon black in the nanocellulose solution, the concentration of carbon black is 2-6wt%, and then adding polytetrafluoroethylene to the solution to a concentration of 20-40wt%, to obtain a modified carbon black slurry;

[0006] Step 2: Spray the modified carbon black slurry evenly onto the surface of the carbon paper and ensure that the carbon loading on the surface of the carbon paper reaches 1 mg / cm 2 ~1.5mg / cm 2 , then dried at room temperature;

[0007] Step 3: After drying, place the carbon paper in a muffle furnace at 240-260°C for 20-40 minutes to remove the active agent on the surface of polytetrafluoroethylene, then increase the temperature to 340-360°C at a heating rate of 3-8°C / min and keep it for 20-40 minutes to sinter the polytetrafluoroethylene and firmly bond the carbon black particles in the carbon paper to obtain a microporous layer.

[0008] In the above-mentioned method for preparing a microporous layer for a fuel cell by using nanocellulose-modified carbon black, in step 1, the nanocellulose solution is prepared by adding CNF nano-microfibrillated cellulose or CNC cellulose nanocrystals to anhydrous ethanol, and then dispersing the solution at 10,000 r / min for 5 minutes using a high-speed dispersing instrument.

[0009] In the aforementioned method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, in step 1, the content of the nanocellulose solution is 0.5wt% or 2.5wt%.

[0010] In the aforementioned method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, in step 1, the length of the nanocellulose is 500 nm-20 μm.

[0011] In the aforementioned method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, in step 1, the nanocellulose solution is poured into a container containing carbon black, and stirred continuously at a speed of 1000 r / min for 2 hours with the assistance of a magnetic stirrer, and ultrasonically treated for 30 minutes to ensure that the carbon black is evenly dispersed in the nanocellulose solution.

[0012] In the aforementioned method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, after the carbon black is evenly dispersed in the nanocellulose solution, polytetrafluoroethylene is added and the mixture is stirred for 20 minutes using a magnetic stirrer until a uniform modified carbon black slurry is formed.

[0013] In the above-mentioned method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, in step 2, the carbon loading on the surface of the carbon paper is 1.25 mg / cm 2 .

[0014] In the aforementioned method for preparing a microporous layer for a fuel cell by using nanocellulose-modified carbon black, in step 3, the carbon paper is placed in a muffle furnace and maintained at 250°C for 30 minutes, then the temperature is increased to 350°C at a heating rate of 5°C / min and maintained for 30 minutes.

[0015] Compared with the prior art, the present invention selects nanocellulose because of its high specific surface area and special nanostructure, so that it can be used as an efficient pore-forming agent to improve the pore structure of the microporous layer in the gas diffusion layer, and can provide more refined pore structure control, thereby optimizing the transmission of water and gas. The nanocellulose used in the present invention has high crystallinity and good mechanical properties, which also makes it play a role in enhancing the performance of the gas diffusion layer. Therefore, the present invention applies nanocellulose to carbon paper, which can promote the separation of gas-liquid two-phase transmission, thereby improving the mass transfer capacity of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 SEM and Leica morphology images of gas diffusion layers prepared from nanocellulose of different forms, where (a) is the surface morphology of Toray carbon paper; (b) VXC; (c) VXC / CNC cellulose nanocrystals-20; (d) VXC / CNF nanofibrillated cellulose 1-20; (e) VXC / CNF nanofibrillated cellulose 1-5; (f) VXC / CNF nanofibrillated cellulose 2-20;

[0017] Figure 2 MPL air permeability at 400MPa;

[0018] Figure 3 It is the air permeability of MPL under different pressures;

[0019] Figure 4 The porosity of the gas diffusion layer MPL prepared for nanocellulose of different morphologies;

[0020] Figure 5 Pore ​​size distribution of gas diffusion layer MPL prepared for nanocellulose with different morphologies. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but they are not intended to limit the present invention.

[0022] Example 1: A method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, comprising the following steps:

[0023] Step 1, adding nano-microfibrillated cellulose (CNF nano-microfibrillated cellulose) with a length of 5 μm to anhydrous ethanol, and then using a high-speed dispersing instrument to disperse at 10000 r / min for 5 minutes to obtain a 0.3wt% nanocellulose solution; then adding carbon black to the nanocellulose solution, with the assistance of a magnetic stirrer, stirring at a speed of 1000 r / min for 2 hours, and ultrasonic treatment for 30 minutes to ensure that the carbon black can be evenly dispersed in the solution, the concentration of the dispersed carbon black is 2wt%, and then adding polytetrafluoroethylene to the solution to a concentration of 20wt%, and continue to stir with a magnetic stirrer for 20 minutes at any time to obtain a modified carbon black slurry;

[0024] Step 2: Cut the Toray carbon paper into 5cm*5cm size, and use a spray gun to evenly spray the carbon black slurry on the surface of the carbon paper. After spraying, weigh the carbon paper immediately to ensure that the carbon loading reaches 1mg / cm 2 , and then dried naturally at room temperature for 3 hours;

[0025] Step 3: After drying, place the carbon paper in a muffle furnace at 240°C for 25 minutes to remove the active agent on the surface of polytetrafluoroethylene. Then, heat the temperature to 345°C at a heating rate of 4°C / min and keep it for 25 minutes to sinter the polytetrafluoroethylene and firmly bond the carbon black particles in the carbon paper. Finally, let it cool naturally to obtain a microporous layer (MPL).

[0026] Example 2: A method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, comprising the following steps:

[0027] Step 1, adding cellulose nanocrystals (CNC cellulose nanocrystals) with a length of 500nm to anhydrous ethanol, and then using a high-speed dispersing instrument to disperse at 10000r / min for 5min to obtain a 1.0wt% nanocellulose solution; then adding carbon black to the nanocellulose solution, with the assistance of a magnetic stirrer, stirring at a speed of 1000r / min for 2h, and ultrasonic treatment for 30min to ensure that the carbon black can be evenly dispersed in the solution, the concentration of the dispersed carbon black is 4wt%, and then adding polytetrafluoroethylene to the solution to a concentration of 30wt%, and continuing to stir with a magnetic stirrer for 20min at any time to obtain a modified carbon black slurry;

[0028] Step 2: Cut the Toray carbon paper into 5cm*5cm size, and use a spray gun to evenly spray the carbon black slurry on the surface of the carbon paper. After spraying, weigh the carbon paper immediately to ensure that the carbon loading reaches 1.5mg / cm 2 , and then dried naturally at room temperature for 3 hours;

[0029] Step 3: After drying, place the carbon paper in a muffle furnace at 260°C for 40 minutes to remove the active agent on the surface of polytetrafluoroethylene. Then, heat the temperature to 360°C at a rate of 6°C / min and keep it for 35 minutes to sinter the polytetrafluoroethylene and firmly bond the carbon black particles in the carbon paper. Finally, let it cool naturally to obtain a microporous layer (MPL).

[0030] Example 3: A method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, comprising the following steps:

[0031] Step 1, adding cellulose nanocrystals (CNC cellulose nanocrystals) with a length of 500nm to anhydrous ethanol, and then using a high-speed dispersing instrument to disperse at 10000r / min for 5min to obtain a 0.15wt% nanocellulose solution; then adding carbon black to the nanocellulose solution, with the assistance of a magnetic stirrer, stirring at a speed of 1000r / min for 2h, and ultrasonic treatment for 30min to ensure that the carbon black can be evenly dispersed in the solution, the concentration of the dispersed carbon black is 4wt%, and then adding polytetrafluoroethylene to the solution to a concentration of 30wt%, and continuing to stir with a magnetic stirrer for 20min at any time to obtain a modified carbon black slurry;

[0032] Step 2: Cut the Toray carbon paper into 5cm*5cm size, and use a spray gun to evenly spray the carbon black slurry on the surface of the carbon paper. After spraying, weigh the carbon paper immediately to ensure that the carbon loading reaches 1.5mg / cm 2 , and then dried naturally at room temperature for 3 hours;

[0033] Step 3: After drying, place the carbon paper in a muffle furnace at 255°C for 30 minutes to remove the active agent on the surface of polytetrafluoroethylene. Then, heat the temperature to 350°C at a heating rate of 4°C / min and keep it for 20 minutes to sinter the polytetrafluoroethylene and firmly bond the carbon black particles in the carbon paper. Finally, let it cool naturally to obtain a microporous layer (MPL).

[0034] Example 4: A method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, comprising the following steps:

[0035] Step 1, adding nano-microfibrillated cellulose (CNF nano-microfibrillated cellulose) with a length of 20 μm to anhydrous ethanol, and then using a high-speed dispersing instrument to disperse at 10000 r / min for 5 minutes to obtain a 0.25wt% nanocellulose solution; then adding carbon black to the nanocellulose solution, with the assistance of a magnetic stirrer, stirring at a speed of 1000 r / min for 2 hours, and ultrasonic treatment for 30 minutes to ensure that the carbon black can be evenly dispersed in the solution, the concentration of the dispersed carbon black is 6wt%, and then adding polytetrafluoroethylene to the solution to a concentration of 40wt%, and continue to stir with a magnetic stirrer for 20 minutes at any time to obtain a modified carbon black slurry;

[0036] Step 2: Cut the Toray carbon paper into 5cm*5cm size, and use a spray gun to evenly spray the carbon black slurry on the surface of the carbon paper. After spraying, weigh the carbon paper immediately to ensure that the carbon loading reaches 1.25mg / cm 2 , and then dried naturally at room temperature for 3 hours;

[0037] Step 3: After drying, place the carbon paper in a muffle furnace at 250°C for 35 minutes to remove the active agent on the surface of polytetrafluoroethylene. Then, heat the temperature to 350°C at a heating rate of 8°C / min and keep it for 40 minutes to sinter the polytetrafluoroethylene and firmly bond the carbon black particles in the carbon paper. Finally, let it cool naturally to obtain a microporous layer (MPL).

[0038] Example 5: A method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, comprising the following steps:

[0039] Cellulose nanocrystals (CNC cellulose nanocrystals) with a length of 500 nm are added to anhydrous ethanol, and then dispersed at 10000 r / min for 5 minutes using a high-speed dispersing instrument to obtain a 2.0wt% nanocellulose solution; then carbon black is added to the nanocellulose solution, and stirred at a speed of 1000 r / min for 2 hours with the assistance of a magnetic stirrer, and ultrasonically treated for 30 minutes to ensure that the carbon black can be evenly dispersed in the solution, and the concentration of the dispersed carbon black is 5.6wt%, and polytetrafluoroethylene is added to the solution to a concentration of 30wt%, and the solution is continuously stirred with a magnetic stirrer for 20 minutes to obtain a modified carbon black slurry;

[0040] Step 2: Cut the Toray carbon paper into 5cm*5cm size, and use a spray gun to evenly spray the carbon black slurry on the surface of the carbon paper. After spraying, weigh the carbon paper immediately to ensure that the carbon loading reaches 1.25mg / cm 2 , and then dried naturally at room temperature for 3 hours;

[0041] Step 3: After drying, the carbon paper is placed in a muffle furnace at 250°C for 30 minutes to remove the active agent on the surface of polytetrafluoroethylene. The temperature is then increased to 350°C at a heating rate of 5°C / min and kept for 30 minutes to sinter the polytetrafluoroethylene and firmly bond the carbon black particles in the carbon paper. Finally, it is allowed to cool naturally to obtain a microporous layer (MPL) (named VXC / CNC cellulose nanocrystals-20, where 20 represents the content of the nanocellulose solution).

[0042] Example 6: A method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, comprising the following steps:

[0043] Nanofibrillated cellulose (CNF nanofibrillated cellulose) with a length of 10 μm is added to anhydrous ethanol, and then dispersed at 10000 r / min for 5 minutes using a high-speed dispersing instrument to obtain a 0.5wt% nanocellulose solution; then carbon black is added to the nanocellulose solution, and with the assistance of a magnetic stirrer, the solution is continuously stirred at a speed of 1000 r / min for 2 hours, and ultrasonically treated for 30 minutes to ensure that the carbon black can be evenly dispersed in the solution, and the concentration of the dispersed carbon black is 5.6wt%, and polytetrafluoroethylene is added to the solution to a concentration of 30wt%, and the solution is continuously stirred with a magnetic stirrer for 20 minutes at any time to obtain a modified carbon black slurry;

[0044] Step 2: Cut the Toray carbon paper into 5cm*5cm size, and use a spray gun to evenly spray the carbon black slurry on the surface of the carbon paper. After spraying, weigh the carbon paper immediately to ensure that the carbon loading reaches 1.25mg / cm 2 , and then dried naturally at room temperature for 3 hours;

[0045] Step 3: After drying, the carbon paper is placed in a muffle furnace at 250°C for 30 minutes to remove the active agent on the surface of polytetrafluoroethylene, and then the temperature is raised to 350°C at a heating rate of 5°C / min and kept for 30 minutes to sinter the polytetrafluoroethylene and firmly bond the carbon black particles in the carbon paper, and finally allowed to cool naturally to obtain a microporous layer (MPL). (Named VXC / CNC cellulose nanocrystals 1-20, where 20 represents the content of the nanocellulose solution).

[0046] Example 7: A method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, comprising the following steps:

[0047] Cellulose nanocrystals (CNC cellulose nanocrystals) with a length of 500 nm are added to anhydrous ethanol, and then dispersed at 10000 r / min for 5 minutes using a high-speed dispersing instrument to prepare a 0.5wt% nanocellulose solution; then carbon black is added to the nanocellulose solution, and with the assistance of a magnetic stirrer, the solution is continuously stirred at a speed of 1000 r / min for 2 hours, and ultrasonically treated for 30 minutes to ensure that the carbon black can be evenly dispersed in the solution, and the concentration of the dispersed carbon black is 5.6wt%, and polytetrafluoroethylene is then added to the solution to a concentration of 30wt%, and the solution is continuously stirred with a magnetic stirrer for 20 minutes at any time to obtain a modified carbon black slurry;

[0048] Step 2: Cut the Toray carbon paper into 5cm*5cm size, and use a spray gun to evenly spray the carbon black slurry on the surface of the carbon paper. After spraying, weigh the carbon paper immediately to ensure that the carbon loading reaches 1.25mg / cm 2 , and then dried naturally at room temperature for 3 hours;

[0049] Step 3: After drying, the carbon paper is placed in a muffle furnace at 250°C for 30 minutes to remove the active agent on the surface of polytetrafluoroethylene, and then the temperature is raised to 350°C at a heating rate of 5°C / min and kept for 30 minutes to sinter the polytetrafluoroethylene and firmly bond the carbon black particles in the carbon paper, and finally allowed to cool naturally to obtain a microporous layer (MPL). (Named VXC / CNC cellulose nanocrystals 1-5, where 5 represents the content of the nanocellulose solution).

[0050] Example 8: A method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, comprising the following steps:

[0051] Cellulose nanocrystals (CNC cellulose nanocrystals CNF nanofibrillated cellulose) with a length of 500 nm are added to anhydrous ethanol, and then dispersed at 10000 r / min for 5 minutes using a high-speed dispersing instrument to obtain a 0.20wt% nanocellulose solution; then carbon black is added to the nanocellulose solution, and stirred at a speed of 1000 r / min for 2 hours with the assistance of a magnetic stirrer, and ultrasonically treated for 30 minutes to ensure that the carbon black can be evenly dispersed in the solution, and the concentration of the dispersed carbon black is 5.6wt%, and polytetrafluoroethylene is added to the solution to a concentration of 30wt%, and the solution is continuously stirred with a magnetic stirrer for 20 minutes to obtain a modified carbon black slurry;

[0052] Step 2: Cut the Toray carbon paper into 5cm*5cm size, and use a spray gun to evenly spray the carbon black slurry on the surface of the carbon paper. After spraying, weigh the carbon paper immediately to ensure that the carbon loading reaches 1.25mg / cm 2 , and then dried naturally at room temperature for 3 hours;

[0053] Step 3: After drying, the carbon paper is placed in a muffle furnace at 250°C for 30 minutes to remove the active agent on the surface of polytetrafluoroethylene, and then the temperature is raised to 350°C at a heating rate of 5°C / min and kept for 30 minutes to sinter the polytetrafluoroethylene and firmly bond the carbon black particles in the carbon paper, and finally allowed to cool naturally to obtain a microporous layer (MPL). (Named VXC / CNC cellulose nanocrystals 2-20, where 20 represents the content of the nanocellulose solution).

[0054] In Examples 1-8 of the present invention, the raw materials are as follows:

[0055] Commercial carbon paper (Toray TGP-H-0605wt% PTFE) was purchased from Toray, Japan, with a thickness of 0.19 mm and a bulk density of 0.44 g / cm 3 , porosity 78%, air permeability 1900cm 2 ·hr·mmAq, plane resistivity 5.8mΩ·cm, tensile strength 50MPa. Anhydrous ethanol (Shanghai Lingfeng Chemical Reagent Co., Ltd.), Cabot Carbon Black Vulcan XC 72R (Cabot Corporation, USA), CNF Nano-microfibrillated cellulose (Tianjin Mujingling Biotechnology Co., Ltd.), CNC Cellulose Nanocrystals (Tianjin Mujingling Biotechnology Co., Ltd.) PTFE 60wt% (Shanghai McLean Biochemical Technology Co., Ltd.)

[0056] Example 9: Testing and characterization, the following experiments were conducted using commercial carbon paper, carbon black (named VXC) and the finished gas diffusion layers of Examples 5 to 8 (VXC / CNC cellulose nanocrystals-20, VXC / CNF nanofibrillated cellulose 1-20, VXC / CNF nanofibrillated cellulose 1-5, VXC / CNF nanofibrillated cellulose 2-20, respectively):

[0057] 1. Microstructure SEM

[0058] The samples were cut to the appropriate size, and the samples with regular shapes were selected for sample preparation. Then, the samples were fixed on the sample stage in turn using conductive glue. The gold layer was sprayed on the sample surface, and the surface morphology of the samples was observed in a vacuum environment using a scanning electron microscope (SEM, SU-1510, Hitachi, Japan) at a voltage of 5kV-15kV. Representative areas were selected and images were taken at different magnifications. Figure 1 SEM and Leica morphology images of gas diffusion layers prepared from nanocellulose of different forms, where (a) is the surface morphology of Toray carbon paper; (b) VXC; (c) VXC / CNC cellulose nanocrystal-20; (d) VXC / CNF nanofibrillated cellulose 1-20; (e) VXC / CNF nanofibrillated cellulose 1-5; (f) VXC / CNF nanofibrillated cellulose 2-20. Figure 1 (a) It can be seen that the surface of Toray carbon paper shows a large number of macroporous structures composed of carbon fibers. Figure 1 (b-f) It can be seen that the surface of the gas diffusion layer covered with MPL is relatively flat overall, with irregular pore structures in some parts, forming more small pores. Because VXC aggregates on the surface, a fine layered structure is formed, and as the length of the nanocellulose fibers increases, the number of uniform micropores gradually increases. The possible reasons for this phenomenon are: during the sintering process, the entire MPL structure is retained, but during the pyrolysis process, the nanocellulose gradually evaporates, the viscosity of the coating surface gradually increases, and the fluidity is lost. However, the entire structure of the MPL with carbon black accumulation is still maintained, making the bonding between the carbon blacks tighter, so evenly distributed pores appear at the original position.

[0059] 2. Breathability

[0060] According to GB / T 20042.7-2014, the air permeability of the sample was analyzed using an air permeability tester (FX3000, Switzerland). The test sample was placed in the test device, the size of the carbon paper was 8cm*8cm, and the test area was selected as 20cm 2, input different test pressures, press the test switch, ensure that the instrument readings are stable, and then record the data. To ensure the accuracy of the measurement results, perform five air permeability tests on each sample and take the average value of the data to reduce errors. Figure 2 MPL air permeability at 400MPa; Figure 3 is the air permeability of MPL under different pressures. Figure 2 and Figure 3 It can be seen that under the same pressure, the average air permeability of VXC / CNF nanofibrillated cellulose 1-20 is 280 L·m -2 ·s -1 As the pressure of the air permeability tester gradually increased, the air permeability of each sample gradually increased, and the higher the test pressure, the more obvious the difference in air permeability. The air permeability of the VXC / CNF nano-microfibrillated cellulose 1-20 group can reach up to 990L·m at 800MPa. -2 ·s -1 The reason for this change may be that the MPL with added nanocellulose becomes volatile gas after heat treatment and escapes, so the pores between carbon black increase, increasing the air permeability of GDL, which indicates that the addition of nanocellulose helps to form more pore structures, thereby improving the air permeability of GDL.

[0061] 3. Porosity and pore size distribution

[0062] The pore structure of the carbon paper is tested using a fully automatic mercury intrusion instrument (Micromeritics AutoPore V 9620, USA). Test principle: The amount of Hg that enters the pores of the material under different pressures can be used to determine the pore volume of the corresponding pore size. During the test, the sample is placed in the mercury intrusion instrument, and then the pressure of mercury is gradually increased. By detecting the pressure change, the size, distribution and surface properties of the sample pores can be determined. Figure 4 The porosity of the gas diffusion layer MPL prepared for nanocellulose of different morphologies; Figure 5 The pore size distribution of the gas diffusion layer MPL prepared for different morphologies of nanocellulose. Figure 4 It can be seen that the porosity of MPL in Example 6 is 75.59%, which is significantly improved compared with VXC. Figure 5 It can be seen that when nanocellulose is introduced as a pore-forming agent, the pore size distribution of the microporous layer shifts to the microporous region. This change indicates that the proportion of micropores and small pores in the microporous layer increases. The increased micropores and small pores provide more channels, which help promote the discharge of water, thereby improving the water management capacity of the gas diffusion layer, and the pore structure of the GDL is optimized.

[0063] The present invention selects nanocellulose because of its high specific surface area and special nanostructure, so that it can be used as an efficient pore-forming agent to improve the pore structure of the microporous layer in the gas diffusion layer, and can provide more refined pore structure control, thereby optimizing the transmission of water and gas. The high crystallinity and good mechanical properties of the nanocellulose used in the present invention also make it play a role in enhancing the performance of the gas diffusion layer. Therefore, nanocellulose can not only improve the performance of the gas diffusion layer, but also help to achieve more green and sustainable energy technology.

Claims

1. A method for preparing a microporous layer for a fuel cell by modifying carbon black with nanocellulose, characterized in that: The steps include: Step 1, preparing a 0.1-2.5wt% nanocellulose solution, uniformly dispersing carbon black in the nanocellulose solution, the concentration of carbon black is 2-6wt%, and then adding polytetrafluoroethylene to the solution to a concentration of 20-40wt%, to obtain a modified carbon black slurry; Step 2: Spray the modified carbon black slurry evenly onto the surface of the carbon paper and ensure that the carbon loading on the surface of the carbon paper reaches 1 mg / cm 2 ~1.5mg / cm 2 , then dried at room temperature; Step 3: After drying, place the carbon paper in a muffle furnace at 240-260°C for 20-40 minutes to remove the active agent on the surface of polytetrafluoroethylene, then increase the temperature to 340-360°C at a heating rate of 3-8°C / min and keep it for 20-40 minutes to sinter the polytetrafluoroethylene and firmly bond the carbon black particles in the carbon paper to obtain a microporous layer.

2. The method for preparing a microporous layer for a fuel cell by using nanocellulose modified carbon black according to claim 1, characterized in that: In step 1, the nanocellulose solution is prepared by adding CNF nano-microfibrillated cellulose or CNC cellulose nanocrystals into anhydrous ethanol, and then dispersing the solution at 10,000 r / min for 5 minutes using a high-speed dispersing instrument.

3. The method for preparing a microporous layer for a fuel cell by using nanocellulose modified carbon black according to claim 1, characterized in that: In step 1, the content of the nanocellulose solution is 0.5wt% or 2.5wt%.

4. The method for preparing a microporous layer for a fuel cell by using nanocellulose modified carbon black according to claim 1, characterized in that: In step 1, the length of the nanocellulose is 500nm-20μm.

5. The method for preparing a microporous layer for a fuel cell by using nanocellulose modified carbon black according to claim 1, characterized in that: In step 1, the nanocellulose solution is poured into a container containing carbon black, and stirred continuously at a speed of 1000 r / min for 2 h with the assistance of a magnetic stirrer, and ultrasonically treated for 30 min to ensure that the carbon black is evenly dispersed in the nanocellulose solution.

6. The method for preparing a microporous layer for a fuel cell by using nanocellulose modified carbon black according to claim 5, characterized in that: After the carbon black was evenly dispersed in the nanocellulose solution, polytetrafluoroethylene was added and continued to be stirred with a magnetic stirrer for 20 min until a uniform modified carbon black slurry was formed.

7. The method for preparing a microporous layer for a fuel cell by using nanocellulose modified carbon black according to claim 1, characterized in that: In step 2, the carbon loading on the carbon paper surface is 1.25 mg / cm 2 .

8. The method for preparing a microporous layer for a fuel cell by using nanocellulose modified carbon black according to claim 1, characterized in that: In step 3, the carbon paper is placed in a muffle furnace and maintained at 250° C. for 30 min, then the temperature is increased to 350° C. at a heating rate of 5° C. / min and maintained for 30 min.